2018
DOI: 10.1093/abbs/gmx129
|View full text |Cite
|
Sign up to set email alerts
|

Feedback regulation of TGF-β signaling

Abstract: Transforming growth factor beta (TGF-β) is a multi-functional polypeptide that plays a critical role in regulating a broad range of cellular functions and physiological processes. Signaling is initiated when TGF-β ligands bind to two types of cell membrane receptors with intrinsic Ser/Thr kinase activity and transmitted by the intracellular Smad proteins, which act as transcription factors to regulate gene expression in the nucleus. Although it is relatively simple and straight-forward, this TGF-β/Smad pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 184 publications
2
79
0
Order By: Relevance
“…In this section, we describe the mechanisms of intracellular signaling of TGF-β, abnormalities of which play critical roles in the development of cancer [18][19][20].…”
Section: Intracellular Tgf-β Signalingmentioning
confidence: 99%
“…In this section, we describe the mechanisms of intracellular signaling of TGF-β, abnormalities of which play critical roles in the development of cancer [18][19][20].…”
Section: Intracellular Tgf-β Signalingmentioning
confidence: 99%
“…In our study, we further demonstrated that TGF‐β1 upregulates ST3Gal1 to circumvent the negative impact of VASN, which in turn trigger MMPs, FGFs expression to support angiogenesis in tumor. This finding reveals a noval glycosylation‐mediated feedback loop to the known regulatory mechanisms of the TGF‐β/Smad signaling system …”
Section: Discussionmentioning
confidence: 77%
“…TGF‐β, Activin, Nodal and Lefty fall into the TGF‐β subclass, while the majority of BMPs, GDFs and AMH constitute the BMP subclass. All of these cytokines transduce signals by binding to serine/threonine kinase receptors on the cell membrane, leading to the phosphorylation and activation of Smad proteins . In total, there are eight Smad proteins in mammalians, which are functionally classified into three subgroups: R‐Smads (receptor‐regulated Smads), Co‐Smad (common Smad, Smad4) and inhibitory Smads (I‐Smads, Smad6 and Smad7) .…”
Section: Cxxc5 Functions As a Signaling Regulator And Mediatormentioning
confidence: 99%
“…Another important point to understand the pleiotropic nature of TGF‐β is the spatiotemporal regulatory mechanisms of the signal transduction process . Feedback regulation plays a pivotal role, fine‐tuning signaling robustness and duration . With respect to it, the two inhibitory Smads have been shown critical in controlling TGF‐β/BMP signaling through negative feedback mechanisms .…”
Section: Cxxc5 Functions As a Signaling Regulator And Mediatormentioning
confidence: 99%